2011
DOI: 10.1074/jbc.m111.229369
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Deficiency of Low Density Lipoprotein Receptor-related Protein-1 Reduces High Density Lipoprotein Secretion and Plasma Levels in Mice

Abstract: The low density lipoprotein receptor-related protein-1 (LRP1) is known to serve as a chylomicron remnant receptor in the liver responsible for the binding and plasma clearance of apolipoprotein E-containing lipoproteins. Previous in vitro studies have provided evidence to suggest that LRP1 expression may also influence high density lipoprotein (HDL) metabolism. The current study showed that liver-specific LRP1 knock-out (hLrp1 Low density lipoprotein receptor-related protein-1 (LRP1), 2 the largest member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 51 publications
3
48
1
Order By: Relevance
“…However, because other mechanisms that are associated with the change in serum triglyceride level have been illustrated in diabetes (Bell et al 2011) and thiazolidinedione treatment (Hanefeld 2009), our in vivo data cannot conclude a causal relationship between hepatic LRP1 expression and serum triglyceride level. In addition, previous studies reported that hepatic LRP1 deficiency did not influence serum triglyceride level (Rohlmann et al 1998, Basford et al 2011. In this study, we used OLETF rats fed a high-fat diet as a diabetic animal model whereas previous studies used mice fed a normal chow diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, because other mechanisms that are associated with the change in serum triglyceride level have been illustrated in diabetes (Bell et al 2011) and thiazolidinedione treatment (Hanefeld 2009), our in vivo data cannot conclude a causal relationship between hepatic LRP1 expression and serum triglyceride level. In addition, previous studies reported that hepatic LRP1 deficiency did not influence serum triglyceride level (Rohlmann et al 1998, Basford et al 2011. In this study, we used OLETF rats fed a high-fat diet as a diabetic animal model whereas previous studies used mice fed a normal chow diet.…”
Section: Discussionmentioning
confidence: 99%
“…LRP1 is also critical for lipid transport and metabolism in adipocytes (12,41,42). It improves the hepatic HDL/ LDL secretion ratio (43) and protects hepatocytes from lipotoxic insults (44). Based on these reports in the literature, LRP1 clearly performs unique functions in a cell type-specific way.…”
Section: Discussionmentioning
confidence: 99%
“…Animals and Tissue Analysis-Liver-specific LRP1-null (hLrp1 cre recombinase transgenic mice in C57BL/6 background (Jackson Laboratory, Bar Harbor, ME) as described previously (13). The animals were maintained under controlled environmental conditions with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, LRP1 has dual signal transduction and cargo endocytosis functions in adipocyte biology. In hepatocytes, in addition to chylomicron remnants and protease complex clearance, LRP1 is also required to complement the mannose 6-phosphate receptor for appropriate lysosomal enzyme trafficking, and its defect impairs prosaposin activation, leading to reduced ABCA1 cell surface translocation and lower HDL secretion (13).…”
mentioning
confidence: 99%